Husband’s Role In Contraception Selection: Scoping Review - St. Mukarromah; Andari Wuri Astuti (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Contraceptives (KB) have various types of methods with advantages and disadvantages in their use. Husband's support is needed because it can provide motivation and comfort in choosing contraception. The results of the BKKBN mini survey show that men's participation in family planning has decreased, namely 11.1% in 2018, down to 8.9%. in 2017 husband's participation in selecting and using contraceptives was still low at 1.3%. Purpose: to map available evidence related to the husband's role in choosing contraception. Scoping this review follows the framework of Arksey and O'Malley, which consists of identifying review questions; looking for relevant evidence; selecting relevant studies; map data; and discuss, conclude and report results. PRISMA flowchart is used to display evidence search flow. The results of the review show that there are 10 articles obtained from the search process. This review raises 4 themes, namely the role of the husband in choosing contraception; factors influencing husband's involvement in contraception selection; cause of the lack of participation of husbands and the health system. The husband's role in contraception selection is still not carried out optimally, as a result of the division of roles between husband and wife due to gender bias, therefore innovative efforts are needed to involve husbands in contraception selection.